Evaluation of lipoprotein‐associated phospholipase A2 as a marker for renal microvasculopathy in adolescents with Type 1 diabetes. Issue 1 (5th August 2019) - Seyfarth, J.; Herebian, D.; Reinauer, C.; Baechle, C.; Roden, M.; Holl, R. W.; Reinehr, T.; Mayatepek, E.; Meissner, T.; Rosenbauer, J.
Abstract: Aim: To assess the relevance of lipoprotein‐associated phospholipase A2 activity as a diagnostic and prognostic marker for renal microvascular diseases. Methods: We analysed lipoprotein‐associated phospholipase A2 activity and lysophosphatidylcholine levels (as a surrogate marker of oxidative stress) in 165 adolescents (aged 17.0 ± 2.3 years) with a history of Type 1 diabetes greater than 10 years. Clinical data were obtained from the German/Austrian nationwide Diabetes‐Patients Follow‐up (DPV) registry at blood collection and on average 2.4 ± 1.3 years later at follow‐up. Relationships between lipoprotein‐associated phospholipase A2 activity and clinical, demographic and laboratory variables, lysophosphatidylcholine levels and presence of albuminuria were evaluated by multivariable linear and logistic regression. Results: Lipoprotein‐associated phospholipase A2 activity was higher in male than female adolescents ( P = 0.002). Albuminuria was present in 14% (22/158) of participants at baseline, and 5% (4/86) of participants without albuminuria at baseline developed albuminuria until follow‐up. Lipoprotein‐associated phospholipase A2 activity was associated neither with present nor with incident albuminuria. Lysophosphatidylcholine did not correlate with lipoprotein‐associated phospholipase A2 activity. Cross‐sectional bivariate correlation as well as multivariable linear regression analysis revealed a negative correlation of lipoprotein‐associated phospholipase A2 activity with HbA1c and HDL‐cholesterol. Conclusions: Lipoprotein‐associated phospholipase activity was not associated with surrogate markers for oxidative stress and early diabetic nephropathy. The association of decreased lipoprotein‐associated phospholipase A2 activity with poor glucose control might limit its function as a predictor of micro‐ and macrovascular diseases in Type 1 diabetes. What's new?: High levels of lipoprotein‐associated phospholipase A2 activity have been shown to be strong predictive markers for cardiovascular events and are associated with oxidative stress. In our cohort of adolescents with Type 1 diabetes, lipoprotein‐associated phospholipase A2 was not associated with albuminuria and lysophosphatidylcholine as surrogate markers of diabetic microvascular disease and oxidative stress. By contrast, lipoprotein‐associated phospholipase A2 activity was negatively correlated with HbA1c levels. This negative association of lipoprotein‐associated phospholipase A2 with HbA1c levels may limit its use as a cardiovascular risk marker in people with diabetes.